2021
DOI: 10.1128/spectrum.00197-21
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Hybridization Capture of SARS-CoV-2 and Metagenomics Enables Genetic Variant Discovery and Nasal Microbiome Insights

Abstract: This is the first FDA emergency-use-authorized hybridization capture-based next-generation sequencing (NGS) assay to detect the SARS-CoV-2 genome. Viral metagenomics and the novel hybrid capture NGS-based assay, along with its research-use-only analysis, can provide important genetic insights into SARS-CoV-2 and other emerging pathogens and improve surveillance and early detection, potentially preventing or mitigating new outbreaks.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 46 publications
2
23
0
Order By: Relevance
“…Multiple studies found increases in antimicrobial resistance genes in COVID-19 patients, involving a wide range of resistance mechanisms [44,46,62,69]. Reflecting increased antibiotic usage in more severe patients, Li et al found greater multidrug efflux pumps (SatA and SatB) in more severe patients [46].…”
Section: Functional Characterizations Of the Covid-19 Respiratory Mic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies found increases in antimicrobial resistance genes in COVID-19 patients, involving a wide range of resistance mechanisms [44,46,62,69]. Reflecting increased antibiotic usage in more severe patients, Li et al found greater multidrug efflux pumps (SatA and SatB) in more severe patients [46].…”
Section: Functional Characterizations Of the Covid-19 Respiratory Mic...mentioning
confidence: 99%
“…Reflecting increased antibiotic usage in more severe patients, Li et al found greater multidrug efflux pumps (SatA and SatB) in more severe patients [46]. Ma and coworkers found resistance to penam, penem, and cephalosporin antibiotics was most abundant and unique to COVID-19 compared to Flu B patients and healthy controls [44], while Nagy-Szakal et al found macrolide resistance was most differentially abundant in COVID-19-positive samples [62].…”
Section: Functional Characterizations Of the Covid-19 Respiratory Mic...mentioning
confidence: 99%
“…Using the sequencing strategy, hybrid capture based enrichment of SARS-CoV-2 10 , we succeeded in obtaining 42 viral genomes from the SARS-CoV-2 cases. The cases represented throughout 12 districts of Shanghai, between April and May, 2022.…”
Section: Dear Editormentioning
confidence: 99%
“…A study focused on developing a novel method validated as a “hybrid capture SARS-CoV-2 NGS (Next Generation Sequencing) assay”, designed by a combination of double-stranded DNA biotin-labeled probes and complimentary software. This approach has received emergency-use authorization from the FDA and is found to be greatly useful in the surveillance and early detection of emerging variants, thus aiming at the prevention and mitigation of future outbreaks [ 32 ]. In another study, a fast diagnostic technique was designed using the portable instrument peak PCR.…”
Section: Techniques For Identification Of Hybrid Variantmentioning
confidence: 99%